Impending US spending bust? The role of housing wealth as borrowing collateral - Daniel Cooper (Federal Reserve Bank of Boston, 2009)
Using data from the Panel Study of Income Dynamics, this paper considers the mechanism by which changing house values impact U.S. household spending. The results suggest that house values affect consumption by serving as collateral for households to borrow against to smooth their spending. The results show that the consumption of households who need to borrow against their home equity increases by roughly 11 cents per 1.00 increase in their housing wealth. Changing house values, however, have little effect on the expenditures of households who do not need to borrow to finance their consumption. Based on these results, the paper further finds that declining housing wealth has a relatively small implied negative impact on aggregate consumption expenditures.
Keywords: E21; 330